2019
DOI: 10.1002/jcb.28934
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of curcumin on cytotoxic and teratogenic activity of retinoic acid in mouse embryonic liver

Abstract: Background: Retinoic acid (RA) is a synthetic vitamin derivative. It exerts toxic and teratogenic effects on the development of embryonic organs in dose-and time-dependent manners in mice. Curcumin is a compound obtained from rhizomes of turmeric (Curcuma longa) and has protective effects on teratogenic agents. The current study examined the effects of curcumin on embryos treated with RA. Methods: A total of 24 female NMRI mice (8-week-old pregnant mice) were investigated in the current study. All of them were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
2
6
0
1
Order By: Relevance
“…In the same year (2004), Hodgson, also showed that the exposure to RA caused severe damage to the liver cells and produced hepatotoxicity. Barandeh et al, (2019) results are also in agreement with the results of the current study, they recorded disruption of embryonic liver cells and parenchyma caused by RA intake. But the present results are in disagreement with the results obtained by Aguwa and his colleagues, (2016), they demonstrated that 400 and 500 mg/kg vitamin A treated group recorded non-significant differences in the liver histological features of as compared to the control group.…”
Section: Histological Studies Of the Ra Effects On The Liver Of Adultsupporting
confidence: 93%
See 1 more Smart Citation
“…In the same year (2004), Hodgson, also showed that the exposure to RA caused severe damage to the liver cells and produced hepatotoxicity. Barandeh et al, (2019) results are also in agreement with the results of the current study, they recorded disruption of embryonic liver cells and parenchyma caused by RA intake. But the present results are in disagreement with the results obtained by Aguwa and his colleagues, (2016), they demonstrated that 400 and 500 mg/kg vitamin A treated group recorded non-significant differences in the liver histological features of as compared to the control group.…”
Section: Histological Studies Of the Ra Effects On The Liver Of Adultsupporting
confidence: 93%
“…Result of the present study has shown that both concentrations of RA caused a non-significant decrease in the weight of the liver of the adult female mice if compared with the weight of the control, while in their prenatal fetuses, group of 50 mg RA showed a higher significant decrease in the liver weight compared with the other groups. This result is in agreement with Barandeh et al, (2019), who demonstrated that RA applies toxic effects on the development of the embryonic organ in a dose and time-dependent manner. But the present result was disagreement with Mahassni & Al-Shaikh, (2014) they showed no connection between oral intake of vitamin A and liver weight in rats.…”
Section: Histological Studies Of the Ra Effects On The Liver Of Adultsupporting
confidence: 93%
“…Curcumin is a polyphenolic compound derived from the plant Longa curcuma [ 139 ]. The pharmacological effects of this natural flavonoid include antioxidant [ 140 ], anti-inflammatory [ 141 ], antitumor [ 142 ], anti-diabetic [ 143 ], cardioprotective [ 144 ], hepatoprotective [ 145 ], and protection against ischemic/reperfusion injury [ 146 ]. In addition to improving various neurological disorders, curcumin has strong anti-inflammatory, anti-amyloid and neuroprotective activities [ 147 ].…”
Section: Biomarkers Evaluated In Depression Studiesmentioning
confidence: 99%
“…Curcumin has been extensively studied in various fields, showing a wide range of action, including Antioxidant, anti-inflammatory, anti-toxicant, anti-apoptotic, anti-diabetic and immunomodulatory actions, demonstrated by in vitro studies and animal models, suggest the use of this compound as a therapeutic agent in counteracting several pregnancy complications [44][45][46][47][48][49]. Inflammation, oxidative stress, Reactive Oxygen Species (ROS) generation and apoptosis are common conditions usually found in almost all of the pathological placental conditions mentioned above; for this reason, curcumin could play a key role in improving pregnancy outcome in these complications.…”
Section: Curcumin Effects On Fertilization and Fetal Developmenmentioning
confidence: 99%
“…Placental growth and fetal development are complex processes tightly regulated during pregnancy and are affected by the microenvironment changes due to the exposure to chemical compounds whose effects can be substantially attenuated by the use of antioxidant substances Retinoic Acid (RA) is an oxidative metabolite of vitamin A associated to a group of birth defects called Retinoic Acid Embryopathy (RAE) and consisting of thymic, cardiac, and central nervous system malformations due to a prenatal exposure to RA [58][59][60]. Interestingly, Barandeh and colleagues treated pregnant mice with 10 mg/kg curcumin in the presence or absence of 60 mg/kg RA and highlighted a significant increase in the lengths of crown rump (CR) and embryo weights in the group treated with a combination of curcumin and RA, suggesting a key role of curcumin in antagonizing the side effects of RA [44].…”
Section: Curcumin As Protector Of Cytotoxic and Teratogenic Agentsmentioning
confidence: 99%